The Origins of Jesus-Devotion: A Response to Crispin Fletcher-Louis - Hurtado, Larry W. (Tyndale bulletin, 2010)
The critique of my work on Jesus-devotion by Dr. Fletcher-Louis (in a previous issue of this journal) combines an essentially correct brief summary of some broad contours of my views and a few interesting points for further discussion; but, unfortunately, the main criticisms are often directed against over-simplified or exaggerated portrayals of my views, and also involve at least one serious red herring. In this brief response, therefore, I try to correct and clarify some key matters in the hope of promoting a more productive discussion of the remarkable devotion to Jesus that characterised earliest Christianity.